Foreign Exchange Risk Management under Statement 52, A Research Report/Determining the Functional Currency under Statement 52, A Research Report (Book). - Largay III, James A.; Brief, Richard P. (The Accounting Review, 1987)
Abstract Reviews the books "Foreign Exchange Risk Management under Statement 52, A Research Report," and "Determining the Functional Currency under Statement 52, A Research Report," by Thomas G. Evans and Timothy S. Doupnik.